2007
DOI: 10.1007/s10549-007-9857-4
|View full text |Cite
|
Sign up to set email alerts
|

The discovery and mechanism of action of letrozole

Abstract: Because estrogen contributes to the promotion and progression of breast cancer, a greater understanding of the role of estrogen in breast cancer has led to therapeutic strategies targeting estrogen synthesis, the estrogen receptor, and intracellular signaling pathways. The enzyme aromatase catalyses the final step in estrogen biosynthesis and was identified as an attractive target for selective inhibition. Modern third-generation aromatase inhibitors (AIs) effectively block the production of estrogen without e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
29
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(31 citation statements)
references
References 30 publications
(35 reference statements)
2
29
0
Order By: Relevance
“…The manufacturer has notified that LTZ can worsen hepatic function tests. Hepatic impairment can markedly increase the half-life of LTZ, and caution is required in such patients [31]. We have demonstrated that LTZ increased hepatic enzyme levels and induced hepatotoxicity.…”
Section: Discussionmentioning
confidence: 77%
“…The manufacturer has notified that LTZ can worsen hepatic function tests. Hepatic impairment can markedly increase the half-life of LTZ, and caution is required in such patients [31]. We have demonstrated that LTZ increased hepatic enzyme levels and induced hepatotoxicity.…”
Section: Discussionmentioning
confidence: 77%
“…First, of all the AIs, letrozole is the most potent inhibitor of aromatase by tightly binding to the hem iron of the enzyme complex [12], and it may do so the same with other CYPs involved in human drug metabolism [13]. Second, anastrozole, another nonsteroidal triazole AI, has been shown to inhibit CYP1A2, 2C9, and 3A in vitro, although the K i values (8–10 μM) were much higher than the therapeutic plasma concentration of the drug and the nanomolar concentration needed to inhibit human aromatase (IC 50 = ∼15 nM) [14].…”
Section: Introductionmentioning
confidence: 99%
“…Letrozole is a nonsteroidal inhibitor that inactivates the aromatase enzyme responsible for the synthesis of estrogens by reversibly binding to the heme group of this member of the cytochrome P450 enzymes (1). Aromatase inhibitors have been used as an adjuvant or first-line treatment for hormone-dependent breast cancer in postmenopausal women (2,3).…”
mentioning
confidence: 99%